Additively Manufactured Amplitude Tapered Slotted Waveguide Array Antenna with Horn Aperture for 77GHz - Lomakin, Konstantin; Alhasson, Saif; Gold, Gerald (IEEE Access, 2022)
In this work, a combined frontend of horn and slotted waveguide array antenna serving as feeding subsystem is presented. This setup allows to implement an amplitude taper in one plane while using the horn aperture to shape the far field radiation characteristics in the perpendicular plane independently and tailored to the individual demand of the application. Moreover, the feeding system is implemented as a loop resulting in a standing wave distribution for a wide frequency range in order to increase the antenna bandwidth. Two specimens with different horn apertures are additively manufactured in slotted waveguide technology from UV curable photopolymer resin using a digital light processing 3D printer and subsequently metal coated by electroless silver plating. A relatively large bandwidth of B-10dB=7.2 GHz and a B-15dB of 4.9 GHz is achieved in measurements indicating a relative bandwidth of 9% and 6% respectively. Antenna Gain is characterized as 17.5 and 20.17 dBi in measurements while maintaining a sidelobe level of 20-22.5 dB at 77 GHz and exhibiting a radiation efficiency of 78.9 and 79.4%. The proposed antenna architecture provides a flexible approach for beam shaping in applications where azimuth and elevation planes exhibit different or contrary requirements, e.g. broad vs. narrow field of view - especially suitable for automotive MIMO-radar sensor